Perlindungan Hukum Bagi Konsumen pada Penggunaan Coil Vape yang Tidak Sesuai dengan Standar Kesehatan - Edgar Rahmantyo; Wika Yudha Shanty; Ariyanti; Fathor Rahman (University of Merdeka Malang, 2026)
The development of electronic cigarettes (vapes) in Indonesia has been accompanied by the circulation of supporting components, including vape coils, which are widely sold separately and often without adequate information regarding materials, safety, or legal compliance. This situation creates potential health and economic harms for consumers and raises legal protection issues because specific regulations governing coils remain unclear. This study uses a normative legal method with a statutory and conceptual approach. The findings indicate that consumer protection may be grounded in the right to safety and information, and business liability may be assessed through contractual liability, product liability, and defect-based liability (design, manufacturing, warning/information defects) across the distribution chain.